Practitioner Perspectives on After Action Reports for Cross-Organizational Emergency Preparedness Learning - Boogard, Parry (P.J.) (My University, 2025)
After action reports (AARs) are retrospective reviews intended to summarize perceived strengths and areas of improvements of an organization's response to an emergency incident, event or exercise. Despite their role in capturing and evaluating response strategies and interventions employed by response agencies, very little is known about the role in which AARs can serve to more generally identify and evaluate effective approaches that can be used across the field more broadly, in other words as cross-organizational learning tools. The majority of the limited studies that have been completed in this area of research are content analyses which have explored potential similarities and themes that exist across AARs. These studies have concluded that inadequate report standardization (Davies et al., 2019), difficulty locating and accessing relevant reports (Sundnes, 2014), and insufficient objectivity of findings (Barnett et al., 2021) pose significant challenges to the value and utility of AARs as tools for cross-organizational learning. In order to gain a better understanding of the perceived challenges, strengths, and limitations of their use as cross-organizational learning tools, interview data collected through interviews with 12 emergency management professionals in Seattle, WA, USA, was analyzed and synthesized using the rapid qualitative data analysis method. Study findings indicate that differences in perceived purpose and intention of AARs, staffing and budget deficiencies, and overcomplexity of templated guidance impact AARs’ application as a cross-organizational learning tool to capture and disseminate effective approaches to emergency preparedness and response.
Thesis (Master's)--University of Washington, 2025
Keywords: After action report (AAR); Disaster Research; Emergency Management; Public Health Emergency Preparedness; Public health; Health services